Anti-Interferon Autoantibodies in Adult-Onset Immunodeficiency Syndrome and Severe COVID-19 Infection - Chen, Long-Fang; Yang, Cheng-De; Cheng, Xiao-Bing (Frontiers in Immunology, 2021)
Adult-onset immunodeficiency syndrome due to anti-interferon (IFN)-γ autoantibodies has attracted much attention in recent years. It usually occurs in previously healthy people and usually presents as chronic, recurrent, and hard-to-control infections that can be effectively treated with aggressive antibiotic therapy. Adult-onset immunodeficiency syndrome is also referred to as AIDS-like syndrome. Anti-type I IFN (IFN-I) autoantibodies have been reported to play a significant role in the pathogenesis of coronavirus disease 2019 (COVID-19) and preexisting anti-IFN-I autoantibodies are associated with increased risk of severe COVID-19. This review summarizes the effects of anti-IFN autoantibodies on the susceptibility and severity of various infectious diseases, including SARS-CoV-2 infection. In addition, we discuss the role of anti-IFN autoantibodies in the pathogenesis of autoimmune diseases that are characterized by recurrent infections.